2004
DOI: 10.2108/zsj.21.1153
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Organization in Hemimetabolous Insects

Abstract: ABSTRACT-The circadian system of hemimetabolous insects is reviewed in respect to the locus of the circadian clock and multioscillatory organization. Because of relatively easy access to the nervous system, the neuronal organization of the clock system in hemimetabolous insects has been studied, yielding identification of the compound eye as the major photoreceptor for entrainment and the optic lobe for the circadian clock locus. The clock site within the optic lobe is inconsistent among reported species; in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 84 publications
2
26
0
Order By: Relevance
“…Hemimetabolous insects, such as cockroaches and crickets, have served as good experimental animals because of their relatively large nervous system with identifiable neurons that allow the search for neuronal components of the circadian system in the central nervous system (for a review, see Tomioka and Abdelsalam 2004). For locomotor rhythms, the OL has been recognized as the locus of the circadian pacemaker in cockroaches (Nishiitsutsuji-Uwo and Pittendrigh 1968) and crickets (Sokolove 1975;Tomioka and Chiba 1984;Abe et al 1997), mostly based on surgical experiments that remove, transect, or extirpate the brain structure.…”
Section: Introductionmentioning
confidence: 99%
“…Hemimetabolous insects, such as cockroaches and crickets, have served as good experimental animals because of their relatively large nervous system with identifiable neurons that allow the search for neuronal components of the circadian system in the central nervous system (for a review, see Tomioka and Abdelsalam 2004). For locomotor rhythms, the OL has been recognized as the locus of the circadian pacemaker in cockroaches (Nishiitsutsuji-Uwo and Pittendrigh 1968) and crickets (Sokolove 1975;Tomioka and Chiba 1984;Abe et al 1997), mostly based on surgical experiments that remove, transect, or extirpate the brain structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the cricket, the clock tissue has been identified and the photoreceptor for entrainment has also been clarified with neurobiological techniques (Tomioka and Abdelsalam, 2004). Recent molecular studies have revealed that the cricket clock oscillates with cyclical expression of clock genes, as has been suggested for other insect species, but has some unique features as well (Moriyama et al, 2008;Danbara et al, 2010;Moriyama et al, 2012;Uryu et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…They show clear behavioral rhythms with seasonal modulations and clear photoperiodic responses (Tomioka and Abdelsalam, 2004). Some of these are suitable for surgical manipulation due to their large size, and have been used for search for the circadian clock that drives the physiological rhythms and for the photoreceptors that are necessary for the clock to synchronize with environmental light cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Ocelli apparently only play a minor role in circadian entrainment (Saunders, 1976;Rieger et al, 2003;Tomioka and Abdelsalam, 2004), although nothing is known about this topic in Archaeognatha. Likewise, there is no information on whether the ocelli in Archaeognatha are involved with navigational behaviors, as in ants (Schwarz et al, 2011a,b).…”
Section: Functional Role Of the Ocellimentioning
confidence: 99%